Zero rating in mobile network markets and its economic effects - Dacheneder, Julius (My University, 2019)
This paper introduces the concept of zero-rating specific content (groups) in mobile network markets basically giving consumers access to certain content without data fees. We give an overview of recent literature on zero-rating, define dimensions in which such tariffs can differ and give an introduction to existing zero-rating tariffs. Based on three papers concerning this question we then evaluate economic consequences of zero-rating. Zero-rating allows internet service providers to better price discriminate their consumers based on their content valuations and thus can increase profit. At the same time there is potential for increased welfare for consumers and content service providers as well. Therefore, regulators shouldn’t forbid such practices in general but should rather intervene ex post in case of undesired effects.
Keywords: zero-rating, mobile network markets, price discrimination, regulation